1990
DOI: 10.1002/jsfa.2740510113
|View full text |Cite
|
Sign up to set email alerts
|

A chemical study of Tamarindus indica (Tsamiya) fruits grown in Nigeria

Abstract: The edible part (pulp) Tamarindus indica L (Tsamiya) is a leguminous tree that grows wild in the tropics (De Wit 1966;Duke and Weber 1981). It thrives well in the north of Nigeria, where the fruit is popular. The pulp is widely used for foods and beverages, and the seeds are sometimes used as a soup seasoner.In Nigeria, as in other developing countries, fruits and vegetables constitute the major available food item after cereals and tubers. Information on the chemical composition of Tamarindus indica (Tsamiy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
4
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 2 publications
5
50
4
2
Order By: Relevance
“…The ascorbic acid content of the pulp ranged from 4.55 to 5.20 mg/100 g [4].It has been reported that the ascorbic acid content ranged from 3.0 to 9.0 mg per 100 g flesh from tamarind pod [8]. A similar result was observed by Anonymous [10] and Ishola et al [9]. Singh et al [11,12] reported 5.27 mg/100 g ascorbic acid in seed free wood apple fresh.…”
Section: Chemical Composition Of Tamarind Pulpsupporting
confidence: 66%
See 2 more Smart Citations
“…The ascorbic acid content of the pulp ranged from 4.55 to 5.20 mg/100 g [4].It has been reported that the ascorbic acid content ranged from 3.0 to 9.0 mg per 100 g flesh from tamarind pod [8]. A similar result was observed by Anonymous [10] and Ishola et al [9]. Singh et al [11,12] reported 5.27 mg/100 g ascorbic acid in seed free wood apple fresh.…”
Section: Chemical Composition Of Tamarind Pulpsupporting
confidence: 66%
“…The calcium, phosphorous and iron content (mg %) of fresh pulp ranged from 402 to 405, 147 to 150 and 1.4 to 1.5 respectively [4]. Dried tamarind pulp contained 9mg% of iron 1.3 to 10.9, calcium 81 to 466 and phosphorous 86 to 190 Bhattacharya et al [13] and Ishola et al [9] reported the similar results close to the study. In the present investigation the values of tartaric acid and titratable acidity were on lower side than the values reported in the literature.…”
Section: Chemical Composition Of Tamarind Pulpsupporting
confidence: 55%
See 1 more Smart Citation
“…The average concentration of lead in the pomegranate fruits was 0.19 ± 0.03 mg/100 g-fw, a level that is much lower than the maximum permissible limit of 3 mg/100 g-fw for lead in vegetables and thus falls within the safe limits for consumption as stated by FAO/WHO [45]. This lead level in pomegranate fruits can be attributed to the high traffic of vehicles along the Morogoro road which is near the area of sampling.…”
Section: Heavy Metal Contentmentioning
confidence: 69%
“…The tamarind seed is a waste from processing industry of tamarind contents of 131.3 gkg -1 crude protein nutrient, 67.1 gkg -1 crude fibers, and 48.2 gkg -1 crude fats [1] and also contains many fatty tamarinds [2]. Despite good nutrient quality, the tamarind seeds also have a hard and non-destructive seed shell structure and have anti-nutrient substances in the form of tannins 56.2 gkg -1 and antitrypsin activity of 10.8 gkg -1 are mostly located in testes or skins seeds [1].…”
Section: Introductionmentioning
confidence: 99%